Rashevsky’s dream: A physico-mathematical foundation of history and culture - Salva Duran-Nebreda; Sergi Valverde (Mètode Science Studies Journal: Annual Review)
The popular science fiction series Foundation penned by Isaac Asimov explores the idea that the course of the future of societies is not only predictable but can be engineered as well. In Asimov’s fictional world, a multidisciplinary science called psychohistory combines mathematics, psychology, and history to predict future events. Nicolas Rashevsky, the father of mathematical biology, lent credibility to the existence of universal principles underpinning human cultural evolution using mathematical models. His vision remains to be fully realized, as our capacity to predict and even engineer is very fragmented. Two main obstacles are a misunderstanding of the role of mathematical models and the limitations of current datasets. Recent advances in complex systems research, computer-based simulations, and large-scale databases, are paving the way towards fully developing a mathematical theory of human history.